KEARIFAN LOKAL MASYARAKAT DUSUN SEMBAGIK, DESA SUKADANA, LOMBOK UTARA - Dyah Indraswati; Arif Widodo (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2022)
This study aims to identify the value of local wisdom of the people of Sembagik Hamlet, Sukadana Village, North Lombok Regency, West Nusa Tenggara. The research method used is descriptive qualitative. Data collection was carried out by interviewing one informant to another. The research subjects include cultural experts, academics, and community leaders in Sembagik Hamlet. Data analysis was performed by data reduction, data classification, data display, and concluding. The results showed that Sembagik Hamlet still maintained its ancestral heritage, this can be seen from the buildings in the form of wooden poles, bamboo walls, and thatched grass roofs. They also still adhere to awig-awig and the Wetu Telu Islamic tradition. This hamlet must be preserved because it has the potential to be used as a research laboratory for various fields of science.